PENGUKURAN CAPABILITY LEVEL PADA LAYANAN APLIKASI JAKI (JAKARTA KINI) MENGGUNAKAN FRAMEWORK COBIT 5 DOMAIN APO, DSS, & MEA - Azzah Hanifah (2022)
The government uses technology developments to innovate to improve the quality of smart city-based public services. One of Jakarta's public services that can meet the needs of Jakarta residents is the JAKI (Jakarta Kini) application. Efforts to improve services are needed for users of the benefits of the JAKI application through measuring the level of capability of the JAKI application using the COBIT 5 framework from the user's perspective in the hope of knowing the factors that are not optimal in the JAKI application and producing recommendations as an effort to increase JAKI's capabilities. The research method used is quantitative by distributing questionnaires to 400 respondents using the JAKI application who are domiciled in the city of Jakarta. The domains used in this study focus on the domains and subdomains APO08 (manage relationships), APO12 (manage risk), DSS01 (manage operations), DSS02 (manage service requests and incidents), DSS05 (manage security), and MEA01 (monitor, evaluate, and assessing performance and adjusting) and has gone through the validity test phase with the results of the calculated r value of more than 0.098 and reliability with the results of the cornbarch alpha value of 0.942. The results of the measurement using the COBIT 5 Framework are that the JAKI application is at level 2, which means it is included in the Managed Process category.